Template‐Enabled Biofabrication of Thick 3D Tissues with Patterned Perfusable Macrochannels (Adv. Healthcare Mater. 7/2022). Issue 7 (6th April 2022) - Davoodi, Elham; Montazerian, Hossein; Zhianmanesh, Masoud; Abbasgholizadeh, Reza; Haghniaz, Reihaneh; Baidya, Avijit; Pourmohammadali, Homeyra; Annabi, Nasim; Weiss, Paul S.; Toyserkani, Ehsan; Khademhosseini, Ali
Abstract : 3D Bioprinting Vascularization is key to the prolonged functionality of the organs. Template‐assisted bioprinting enables biofabrication of stand‐alone thick tissues with complex vascularized networks. In article number 2102123 by Ehsan Toyserkani, Ali Khademhosseini, and co‐workers, an indirect printing strategy not only eliminates the need for costly 3D bioprinters, but also allows integration of living cells within the extracellular matrix‐mimicking hydrogel matrices.